Emotional Brand Attachment: A Factor Enhancing Customer-Bank Relationships - ., Yulihardi; ., Muharti; Anita, Rizqa; Rahmat, Adi; Balkish Zakaria, Nor (International Journal of Engineering and Technology, 2018)
The rapid development of business, forcing the banking sector to be able to compete by generating competitive advantage. One way to maintain the existence of a company is to create an emotional attachment with their customers. With these attachments will have an impact on loyalty so as to generate profits for the company. The purpose of this paper is to analyze the effect of trust and involvement toward emotional attachment and bank loyalty. The research was conducted quantitatively with causal and descriptive research design. The amounts of sample are 240 participants. The data analysis technique used is the analysis of Partial Least Square (PLS). The results showed that all dimensions of trust and involvement affect significantly positive toward emotional attachment and bank loyalty.Â